2016
DOI: 10.1177/1759720x16635887
|View full text |Cite
|
Sign up to set email alerts
|

Disease-modifying antirheumatic drugs improve cardiovascular autonomic neuropathy in psoriatic arthritis

Abstract: Background: Cardiovascular autonomic neuropathy (CAN) is a significant risk predictor for sudden cardiac death in autoimmune rheumatic diseases. As yet, there is no therapeutic treatment of CAN in psoriatic arthritis (PsA). Even now, the impact of the most commonly employed disease-modifying antirheumatic drug (DMARD) therapy on CAN in PsA is not known. Hence, we investigated the impact of DMARDs on CAN in PsA. Methods: In this prospective, cross-sectional study, 20 patients of PsA and 20 ageand sex-matched he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…45,46 Moreover, elevated systemic TNFα levels have also been linked to the development of autonomic nervous system dysfunction in animal models 47 and in patients. 48 These observations potentially implicate TNFα as an important link between chronic liver injury, sickness behaviours (including fatigue) and autonomic dysfunction. They also suggest that inhibition of peripheral TNFα production and/or activity in CLD may represent a novel approach for treating fatigue in patients with CLD, and therefore warrants future study.…”
Section: Pathophysiologymentioning
confidence: 99%
“…45,46 Moreover, elevated systemic TNFα levels have also been linked to the development of autonomic nervous system dysfunction in animal models 47 and in patients. 48 These observations potentially implicate TNFα as an important link between chronic liver injury, sickness behaviours (including fatigue) and autonomic dysfunction. They also suggest that inhibition of peripheral TNFα production and/or activity in CLD may represent a novel approach for treating fatigue in patients with CLD, and therefore warrants future study.…”
Section: Pathophysiologymentioning
confidence: 99%
“…We hypothesized that intervention with n-3 PUFA would increase RR. Based on previous literature [33,34] and to achieve α = 0.05 and 1-β = 0.80 we needed a sample size with 63 subjects in each group.…”
Section: Discussionmentioning
confidence: 99%
“…In a small study with 20 patients with PsA, Syngle et al observed improvement in autonomic dysfunction after treatment with different synthetic DMARDs over 12 weeks [33]. However, no treatment strategy for cardiac autonomic dysfunction in PsA has yet been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Variable outcomes and tolerability were reported for DMARDs such as methotrexate (MTX), sulfasalazine, cyclosporin, and intramuscular gold . Leflunomide, also a DMARD, inhibits the synthesis of de novo pyrimidine, following which T cell activation and proliferation is suppressed.…”
Section: Introductionmentioning
confidence: 99%